Usage Pattern of Information and Communication Technology Tools among University Faculty Members - Ziaulhaq Haqyar,; Rohila, Anil Kumar; Joginder Singh Malik,; Ajay Kumar,; Shubham, (Indian Journal of Extension Education, 2025)
ICT boosts teaching by enabling interactive learning, supports research through advanced data analysis and collaboration tools, and enhances extension services with real-time information and communication. This integration ultimately drives innovation and improves agricultural practices and outreach. Keeping this in view, the study was carried out at the CCS Haryana Agricultural University, Hisar in 2021-22 to assess the usage pattern of ICT tools among faculty members of university. Data were collected with the help of well-structured questionnaire, especially developed for the present study. Four colleges i.e., College of Agriculture, College of Agricultural Engineering and Technology, College of Basic Sciences and Humanities, and I.C. College of Home Science were selected purposively for collection of data. Further, 25 faculty members were selected randomly from each selected college. Eleven independent variables included in the study. Data were analysed with the help of Statistical Package for the Social Sciences (SPSS).The study concluded that usage pattern of ICT tools found less for extension activities as compare to personal, teaching and research among faculty members.